2014
DOI: 10.1002/2014ja019958
|View full text |Cite
|
Sign up to set email alerts
|

Annual fractions of high‐speed streams from principal component analysis of local geomagnetic activity

Abstract: We study the latitudinal distribution of geomagnetic activity in 1966–2009 with local geomagnetic activity indices at 26 magnetic observatories. Using the principal component analysis method we find that more than 97% of the variance in annually averaged geomagnetic activity can be described by the two first principal components. The first component describes the evolution of the global geomagnetic activity, and has excellent correlation with, e.g., the Kp/Ap index. The second component describes the leading p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
40
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 31 publications
10
40
0
Order By: Relevance
“…In this paper we have studied the spatiotemporal evolution of geomagnetic activity in 1966–2011 using local A h and IHV indices of 26 stations covering a wide range of latitudes. We analyzed the indices using the principal component analysis method and confirmed that our recent results for the A h indices [ Holappa et al , ] also hold for IHV indices, i.e., that the first PC describes global average geomagnetic activity and the second PC the deviations from the global average caused by high‐speed streams.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…In this paper we have studied the spatiotemporal evolution of geomagnetic activity in 1966–2011 using local A h and IHV indices of 26 stations covering a wide range of latitudes. We analyzed the indices using the principal component analysis method and confirmed that our recent results for the A h indices [ Holappa et al , ] also hold for IHV indices, i.e., that the first PC describes global average geomagnetic activity and the second PC the deviations from the global average caused by high‐speed streams.…”
Section: Discussionsupporting
confidence: 83%
“…The respective EOF1(Ah) and EOF1(IHV) depicted in Figure describe the latitudinal modes associated with the PC1s. As we found earlier [ Holappa et al , ], EOF1(Ah) is almost flat (independent of latitude), meaning that all stations contribute with roughly equal weights to PC1. Hence, the PC1(Ah) is very closely proportional to the average of the 26 A h s indices.…”
Section: Principal Component Analysis Methodssupporting
confidence: 82%
See 2 more Smart Citations
“…On the other hand, when disturbances are directly driven by CMEs around solar maxima, NGK, due to its weaker dependence on B , registers suppressed AhK Z . This is in agreement with recent results of Holappa et al [], where it was demonstrated that the fraction of HSS (CME)‐related activity in annual geomagnetic activity depicts a local maximum (minimum, respectively) at the specific range of midlatitudes where NGK is situated. The different dependence to HSSs versus CMEs was also held accountable for the dominant fraction of observed differences in geomagnetic activity between the geomagnetic stations.…”
Section: Latitudinal Differences Of Geomagnetic Indicesmentioning
confidence: 99%